2014
DOI: 10.1097/01.mnh.0000447013.36475.96
|View full text |Cite
|
Sign up to set email alerts
|

Role of Na/H exchange in insulin secretion by islet cells

Abstract: Purpose of review Sodium/hydrogen exchangers (NHEs) are a large family of transport proteins catalyzing the exchange of cations for protons across lipid bilayer membranes. Several isoforms are expressed in b cells of the endocrine pancreas, including the recently discovered and poorly characterized isoform NHA2. This review will summarize advances in our understanding of the roles of NHEs in the regulation of insulin secretion in b cells. Recent findingsPlasmalemmal full-length NHE1 defends b cells from intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…RNA isolation was performed using Trizol reagent (ThermoFisher Scientific, Waltham, MA, USA) as described [ 5 , 8 ]. Real-time PCR was performed using pre-synthesized Assays-on-Demand (AoD; Life Technologies/ABI, Rotkreuz, Switzerland) on an ABI ViiA 7 System.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA isolation was performed using Trizol reagent (ThermoFisher Scientific, Waltham, MA, USA) as described [ 5 , 8 ]. Real-time PCR was performed using pre-synthesized Assays-on-Demand (AoD; Life Technologies/ABI, Rotkreuz, Switzerland) on an ABI ViiA 7 System.…”
Section: Methodsmentioning
confidence: 99%
“…NHA2, also known as SLC9B2 or NHEDC2, is a recently cloned, poorly characterized NHE isoform [ 3 ]. Previous studies suggested that NHA2 is the correlate of the long sought sodium/lithium countertransporter that was linked to the pathogenesis of diabetes mellitus and essential hypertension in humans [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In murine islets, mRNA of eight NHE isoforms has been found: NHE1, NHE5 through NHE9, as well as NHA1 and NHA2, although only the roles of NHE1 and NHA2 have been studied in detail, beyond the expression level (72, 201, 285). The involvement of NHE1 and NHA2 in β-cell functions have been discussed in detail by Deisl et al (71). In brief, glucose uptake into β cells followed by its metabolism lead to an increase in cellular ATP/ADP ratio which triggers the closure of ATP-sensitive potassium (K ATP ) channels, a main determinant of the β-cell membrane potential.…”
Section: Na+/h+ Exchange In the Exocrine And Endocrine Pancreasmentioning
confidence: 99%
“…Within the digestive organs, NHA1 protein has been detected in the pancreatic β cells, but its role has not been extensively studied (71). NHA2 (also known as Na + /H + exchanger domain-containing protein 2) is expressed more broadly in the digestive tract, where it was detected in the stomach, jejunum, and colon (94).…”
Section: Mammalian Monovalent Cation Proton Antiporter Superfamilymentioning
confidence: 99%
See 1 more Smart Citation